2017
DOI: 10.3390/ma10101113
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Comparison of Different Carbon Fiber Composites in Reinforcement Layouts for Wooden Beams of Historical Buildings

Abstract: This paper offers a detailed, quantitative and exhaustive experimental comparison in terms of mechanical properties of three different layouts of carbon composite materials (CFRP) used to strengthen existing old timber beams highly affected by diverse natural defects and biological attacks, testing the use of pultruded laminate attached on the tension side of the element (LR), CFRP fabrics totally U-shape wrapping the timber element (UR), and the combined use of both reinforcement solutions (UR-P). Moreover, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Many publications [11,12,23,24] reported that using the U-shaped member can effectively improve the maximum bending capacity. Rescalvo et al [19,20] presented data to demonstrate the benefits in flexural strength, and stiffness of timber improved due to the U-shaped member [19,20]. e same results were obtained with applications of the U-shaped member reinforced LVL beam in a study by Subhani et al [25].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Many publications [11,12,23,24] reported that using the U-shaped member can effectively improve the maximum bending capacity. Rescalvo et al [19,20] presented data to demonstrate the benefits in flexural strength, and stiffness of timber improved due to the U-shaped member [19,20]. e same results were obtained with applications of the U-shaped member reinforced LVL beam in a study by Subhani et al [25].…”
Section: Introductionmentioning
confidence: 70%
“…A system of U-shaped member provided to reinforce timber beam shows a ductile behavior with respect to the plate [18][19][20]. e materials such as steel, aluminum, cement asbestos, and GFRP adopted are all available [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising results, external FRP reinforcements have significant disadvantages regarding their structural application, such as visual impact, mechanical damage, and, more importantly, fire sensitivity [35]. For that reason, another line of research has been conducted on the internal FRP reinforcement of wood using bars and sheets with different configurations [36,37]. Following this approach, Raftery and Harte [38] proposed the introduction of GFRP in low-grade glulam timber beams with low reinforcement ratios between 1.10% and 1.25%.…”
Section: State Of the Artmentioning
confidence: 99%
“…Reinforcing wood beams using FRP materials started in the 1960s [ 5 , 6 , 7 ], with GFRP (fiberglass) being proposed to reinforce sawn and glued laminated beams (glulam). Since that date, many papers have been published (see [ 8 ] for a large description of previous results and literature). However, in many previous in situ interventions, the reinforcement of timber structures of historical and non-historical building was carried out without numerical or analytical codes, i.e., following the empirical experience of the manufacturers involved and the data sheets of the FRP suppliers.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of the combination of a laminate strip attached on the tension side and a CFRP fabric discontinuously wrapping the timber element. The experimental study involved small and large timber beams of Pinus Sylvestris L. with many defects [ 8 , 24 ]. A comparison between non-reinforced and Braided reinforced (with unidirectional and bidirectional fabric) small-sized specimens (1.3 m long) was carried out.…”
Section: Introductionmentioning
confidence: 99%